Sound Productivity of Spiny Lobster Panulirus homarus (Linnaeus, 1758) due to Crude Oil Contamination - Hartoyo, Hartoyo; Amron, Amron; Fitri, Aristi Dian Purnama; Darmanto, YS (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2022)
Anthropogenic activities have the potential to put pressure on the marine environment. Crude oil was one of the pressure that give rise to any response of the aquatic organism, such as sound. This study aimed to analyze the sound productivity of spiny lobster Panulirus homarus (Linnaeus, 1758) in waters contaminated with crude oil. Observation of lobster sound was carried out on a laboratory scale using the passive acoustic method. A hydrophone and Closed Circuit Television (CCTV) camera coupled with a decoder and personal computer used to record the movements and sounds of P. homarus during the treatment of crude oil at concentrations 1; 5; 10 and 100 mgL-1. The result showed that crude oil contamination in water was impacted the sound productivity of P. homarus. In the low concentration of crude oil (1 - 5 mgL-1), P. homarus was responded with more sound produced. Afterwar, until concentration off 10 mgL-1, the response of P homarus showed different between individuals. In the 100 mgL-1 concentration, the sound productivity of all P. homarus was decreased. Based on this study, we concluded that the sound of P. homarus has the potential as an indicator of water pollution.Keywords: Panulirus houmarus, crude oil, fish sound